2000
DOI: 10.1002/1521-3919(20000601)9:5<281::aid-mats281>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress analysis for polyimide thin film: The effect of solvent evaporation

Abstract: We propose a stress model to account for the thermal stress caused by a mismatch of isobaric expansivity, solvent evaporation, and imidization. The evaporation strain term is given as functions of a viscosity, and solvent weight fraction. The proposed model is in very good agreement with experimental data and gives useful information about the analysis of the thermal stress caused in polymeric films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This equation indicates that the birefringence of a polymer thin film is proportional to the internal stress, which is usually caused by the spin coated, crosslinking processes, and the mismatch of coefficients of thermal expansion between film and substrate. Previous studies have demonstrated that careful control of solvent evaporation and polymer curing during film heating and cooling processes are effective in partly relieving internal stress that causes thin film optical anisotropy 31. But molecular design is still essential to reduce intrinsic birefringence.…”
Section: Resultsmentioning
confidence: 99%
“…This equation indicates that the birefringence of a polymer thin film is proportional to the internal stress, which is usually caused by the spin coated, crosslinking processes, and the mismatch of coefficients of thermal expansion between film and substrate. Previous studies have demonstrated that careful control of solvent evaporation and polymer curing during film heating and cooling processes are effective in partly relieving internal stress that causes thin film optical anisotropy 31. But molecular design is still essential to reduce intrinsic birefringence.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] Cracking of thin NiAl metal 18 and poly͑methylsilsesquioxane͒ polymer 19 films during cooling part of thermal cycling has been reported. Thermal stresses induced by the thermal expansion mismatch between the thin film material and the silicon substrate cause wafer deformation as depicted in Fig.…”
Section: Cracking Mechanisms Of Photoresistmentioning
confidence: 99%
“…In addition, it is difficult to fabricate patterns with high resolutions and high-precisions in polyimide films because polyimide is difficult to etch or to dissolve away by a conventional photolithography and etching processes [15][16][17]. Furthermore, fine patterns with rectangular cross-sections and well defined line-edges are difficult to achieve due to a large shrinkage (30 -60%) resulting from the thermal imidization reaction of the polyimide precursor [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated multi-layered Cu/PI interconnections were evaluated for their electric properties and the applicability of the interconnections for electric packaging was verified. 5,10,20, and 50 µm widths at a density of 0.5 were fabricated on an 8-inch Si master wafer by photolithography using a photoresist (TOK THMR-iP3650) and a contact mask aligner (EVG EVG6200). The patterns were etched to a depth of 4.2 µ m by an inductively coupled plasma reactive ion etching (ICP-RIE) system (SPP Technologies MUC-21) using SF 6 and C 4 F 8 .…”
Section: Introductionmentioning
confidence: 99%